2008
DOI: 10.1111/j.1939-1676.2008.0149.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sample Quality on the Sensitivity of Endoscopic Biopsy for Detecting Gastric and Duodenal Lesions in Dogs and Cats

Abstract: Background: The quality of histopathology slides of endoscopic biopsies from different laboratories varies, but the effect of biopsy quality on outcome is unknown.Hypothesis: The ability to demonstrate a histologic lesion in the stomach or duodenum of a dog or cat is affected by the quality of endoscopic biopsy samples submitted. More endoscopic samples are needed to find a lesion in poor-quality tissue specimens.Animals: Tissues from 99 dogs and 51 cats were examined as clinical cases at 8 veterinary institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
117
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 11 publications
7
117
0
5
Order By: Relevance
“…Therefore, there is a possibility that the samples for histopathological examination had rich tumor cells, while those for PCR examination had fewer or no tumor cells in the specimen. Furthermore, the quality of the sample is known to affect the result of histopathological diagnostic sensitivity [12], which may lead to a discrepancy between the findings of histopathology and PCR analysis. Five FFPE samples were included in this study; these samples had a potential risk of DNA fragmentation during the process of formalin fixation [1].…”
mentioning
confidence: 99%
“…Therefore, there is a possibility that the samples for histopathological examination had rich tumor cells, while those for PCR examination had fewer or no tumor cells in the specimen. Furthermore, the quality of the sample is known to affect the result of histopathological diagnostic sensitivity [12], which may lead to a discrepancy between the findings of histopathology and PCR analysis. Five FFPE samples were included in this study; these samples had a potential risk of DNA fragmentation during the process of formalin fixation [1].…”
mentioning
confidence: 99%
“…This may have resulted from subtle differences between the biopsy specimens because they were taken from close, but not identical lesions. Moreover, it has been reported that interobserver variation and the quality of endoscopic biopsy specimens influences histopathological outcome [19,20]. Since the endoscopic biopsy specimens were taken by several operators and evaluated by several pathologists, this may have influenced the histopathological diagnoses obtained in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…Endoscopy, which was chosen in the reported dog, is the least invasive technique; it allows inspection of gastric and intestinal mucosa and the collection of multiple samples from different sites (Washabau et al 2010). According to Willard et al (2008), endoscopy can be an effective tool for diagnosing GI mucosal lymphoma in dogs. The samples should be obtained from all endoscopically accessible segments of the GI tract.…”
Section: Discussionmentioning
confidence: 99%